KEWENANGAN DEWAN PERWAKILAN DAERAH REPUBLIK INDONESIA (DPD RI) DALAM MEMPERJUANGKAN PEMEKARAN DAERAH DI PROVINSI RIAU TAHUN 2012-2016 - Setiawan, Aris; Asrida, Wan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This study, entitled "Authority of the Republic of Indonesia Regional Representative Council (DPD) in the Struggle for Regional Expansion in Riau Province Year 2012-2016". This research background with the Indonesian Government Regulation No. 78 Year 2007 on Procedures for the Establishment, Abolition, and merging of Regions, which is in the form DOB (Autonomous Region Baru) must meet all the requirements of both the requisite administrative, technical, and physical territoriality. The formulation of the problem in this research is how the efforts made by DPD in the struggle for regional expansion in Riau Province in 2012-2016 as well as what are the factors that constrain the DPD in the fight for regional expansion in Riau Province in 2012-2016. Issues contained in this research are there areas that will conduct regional division namely Indragiri South (Insel) and Indragiri North is Indragiri Hilir Regency, Gunung Sahilan Darussalam from Kampar, Kota Duri from Bengkalis and Rokan Darussalam carved out of Rokan Hulu has met all the requirements and already have the letter the President agreed to immediately bloomed. The method used in this study is a qualitative method that describes the data descriptively. Data collection techniques used were interviews and secondary data analysis. While the source of the data used are primary data obtained from the study site in the form of research informants and further supported by secondary data.Based on the research that has been done are some of the findings of which are respectively Head of the Region has not issued a recommendation on the area that will form a new autonomous region, the lack of political communication between the Regional Representative Council of the Republic of Indonesia (DPD RI) representative Riau Province with the rest of society, Parliament Regency / City and regional Head associated with its regions will conduct regional expansion, as well as the central government moratorium since June 2014 and to complete the draft Regulation on Design of the regional Planning (PP Desertada).Keyword: The authority of the DPD, PP Desertada, Regional Expansion